ANALYSIS OF AGRICULTURAL LAND USE AND EVALUATION OF IMPACT ON ECONOMIC DEVELOPMENT IN BIJNOR DISTRICT: बिजनौर जनपद में कृषि फसल वितरण का सामाजिक विकास पर प्रभाव एवं नियोजन की आवश्यकता - Sharma Rawal, Rashmi; Kumar, Naresh (International Journal of Research -GRANTHAALAYAH, 2020)
From the beginning of human life, in the gradual development of its culture, various types of enterprises, businesses, economic activities and social development and its basic needs are obtained from the land. The study of the effects on human behavior and human functioning, the distance of the market from agricultural areas, market prices and agricultural production, demand of agricultural areas as well as the capacity of production, land production, density of cropland etc. were the questions that were studied Studies the impacts on agricultural land from a human social point of view. Agriculture is the most important aspect of the rural economy. Agriculture is the backbone of the sustenance and social development of all living communities. Along with the special production method and social ecologies of the area, the agricultural system and farming community, land ownership, availability of resources, size of holdings, agricultural land use along with social change of human environment has also seen changes in the agricultural state. Researchers by evaluating the effects of agricultural land use on social development in their area of ​​study Bijnor district to maintain the quality of land under environmental balance through scientific techniques and green agricultural development for various long term agricultural needs. There is a need and the plains formed from the fertile land by the rivers Ramganga and Kho are important for agricultural land use and crop production.. Hindi: मानव आदिकाल से ही अपनी संस्कृति के क्रमिक विकास में विभिन्न प्रकार के उद्यम, व्यवसायों, आर्थिक क्रियाकलाप एवं सामाजिक विकास तथा अपनी मूलभूत आवश्यकताओं की पूर्ति भूमि से प्राप्त करता है। मानव व्यवहार एवं मानवीय कार्य प्रणाली पर होने वाले प्रभावों का अध्ययन कृषि क्षेत्रों से बाजार की दूरी ,बाजार का भाव एवं कृषि उत्पादन, कृषि क्षेत्रों की मॉंग के साथ-साथ उत्पादन क्षमता भूमि उत्पादन की क्षमता फसल भूमि की सघनता आदि ऐसे प्रश्न रहे जिनका अध्ययन मानव सामाजिक दृष्टि कोण से कृषि भूमि पर पड़ने वाले प्रभावों का अध्ययन करता है। कृषि ग्रामीण अर्थव्यवस्था का सबसे महत्वपूर्ण पक्ष है। कृषि समस्त जीव समुदाय का भरण-पोषण एवं सामाजिक विकास की रीढ़ होती है। फसलोत्पादन क्षेत्र विशेष उत्पादन विधि तथा वहाँ की सामाजिक पारिस्थितियों से कृषि व्यवस्था एवं कृषक समुदाय , भूमि स्वामित्व, संसाधनों की उपलब्धता, जोत का आकार, कृषि भूमि उपयोग को मानवीय वातावरण के सामाजिक परिवर्तन के साथ-साथ कृषि प्रदेश मे भी परिवर्तन देखा गया है। शोधार्थी अपने अध्ययन क्षेत्र बिजनौर जनपद में कृषि भूमि उपयोग का सामाजिक विकास पर प्रभावों का मूल्यांकन करके उसके भावी नियोजन की आवश्यकताओं को दीर्घकालीन विभिन्न कृषि भूमि उपयोग के वैज्ञानिक तकनीक एवं हरित कृषि विकास के माध्यम से वातावरण सन्तुलन के अन्तर्गत भूमि की गुणवत्ता को बनाये रखने की आवश्यकता है तथा रामगंगा और खो नदियों के द्वारा उपजाऊ भूमि से निर्मित मैदान कृषि भूमि उपयोग एवं फसल उत्पादन के लिये महत्वपूर्ण है।